The janus-faced biology of GPNMB: from tissue homeostasis to cancer pathogenesis - Long, Cheng; Yun, Li Qin; Yuan, Ma Dai; Al-Sultan, Imad Ibrahim Ali (Frontiers in Molecular Biosciences, 2025)
Glycoprotein non-metastatic melanoma protein B (GPNMB) is a transmembrane glycoprotein that differentially regulates tissue homeostasis and disease pathogenesis. In physiological contexts, it maintains melanosome biogenesis, osteogenesis, and neuroprotection through domain-specific interactions. Pathologically, tumors exploit GPNMB’s dual mechanisms: membrane-bound isoforms mediate T cell exclusion via DC-HIL/Syndecan-4, while soluble GPNMB(sGPNMB) promote metabolic reprogramming through CD44/NF-κB. Clinically, GPNMB overexpression correlates with poor outcomes, notably demonstrating 40% versus 8% ADC response in high- versus low-expressing TNBC (p < 0.001). Emerging data reveal its crosstalk with HER2/FGFR1 pathways and identify K48-ubiquitination as a therapeutic resistance mechanism. These findings position domain-selective GPNMB targeting as a promising precision oncology strategy.